The Memoirs of Jacques Casanova de Seingalt, Vol. V (of VI), "In London and Moscow" : The First Complete and Unabridged English Translation, Illustrated with Old Engravings - Casanova, Giacomo, 1725-1798; Machen, Arthur, 1863-1947 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Memoirs of Jacques Casanova de Seingalt, Vol. V (of VI), "In London and$1! =(B" by Giacomo Casanova is part of a memoir written beginning in 1789. This volume belongs to Casanova's famous autobiography covering his life as an 18th-century Venetian adventurer. Originally written in French, the complete work spans twelve volumes and chronicles his extraordinary experiences through 1774. The manuscript's tumultuous history includes censorship, mistranslations, and pirated editions before the original version finally emerged in 1960, revealing Casanova's unfiltered account of adventure and intrigue. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Histoire_de_ma_vie
Release date is 2012-03-29
Produced by David Widger
Keywords: Casanova, Giacomo, 1725-1798; Europe -- History -- 18th century -- Biography